Cell-free DNA release following psychosocial and physical stress in women and men - A. S. Limberg; F. Berg; E. Köper; C. Lindgraf; C. Gevers; R. Kumsta; E. M. Hummel; D. A. Moser (Translational Psychiatry)
Abstract Cell-free DNA (cfDNA) is continuously shed by all cells in the body, but the regulation of this process and its physiological functions are still largely unknown. Previous research has demonstrated that both nuclear (cf-nDNA) and mitochondrial (cf-mtDNA) cfDNA levels increase in plasma in response to acute psychosocial and physical stress in males. This study further investigated these findings by testing 31 female participants (16 using oral hormonal contraception and 15 not using oral hormonal contraception), and the results were subsequently compared with those of 16 male participants. In addition, cf-nDNA and cf-mtDNA were comparatively quantified in both plasma and saliva at four time points, 2 min before and 2, 15, and 45 min after stress induction. A novel method was implemented to facilitate the straightforward collection of capillary blood by non-medical personnel for plasma analysis. While cf-mtDNA is readily detectable in body fluids due to its high copy number, the quantification of cf-nDNA is challenging due to its low abundance. To overcome this, a multiplex quantitative polymerase chain reaction (qPCR) protocol targeting L1PA2 elements, which are prevalent in the human genome, was utilized. The analysis indicated significantly elevated levels of cf-nDNA in both plasma and saliva in all participants, irrespective of gender, following psychosocial and physical stress. Conversely, neither plasma nor saliva exhibited a consistent or stress-induced release pattern for cf-mtDNA. CfDNA is a promising biomarker that is consistently released after stress in both men and women and can be detected in both plasma and saliva. However, further research is necessary to elucidate the mechanisms of cfDNA release from specific cells and to understand its biological function in the body.